Uso de lodo compostado e bactérias solubilizadoras na disponibilidade de fósforo e produção de grão-de-bico - Verônica Aparecida Santos Ferreira Soares (2023)
The phosphorus is an essential nutrient for plant development. However, phosphorus sources are finite and non-renewable, making this input increasingly scarce. Therefore, the use of sewage sludge emerges as an alternative phosphorus source, combined with the inoculation of phosphate-solubilizing bacteria, which has been crucial in the pursuit of sustainable production systems. Thus, the objective of the studies was to evaluate the effect of inoculation with Bacillus spp. and the phosphorus availability after the application of organic and mineral sources on the growth, production, nutrient accumulation, and heavy metal content in chickpeas. The experiments were evaluated over two crop cycles, conducted in a randomized block design with four replications, in a 2 x 4 factorial scheme. This scheme included the absence and presence of a mix of Bacillus subtilis sp and B. megaterium sp, alongside four management practices involving organic and mineral phosphorus sources: no fertilization (Test); mineral fertilization with 150 kg ha-1 of P2O5 in the form of single superphosphate (SS); organic fertilization with 150 kg ha-1 of P2O5 in the form of sewage sludge (LC); and a mix of mineral and organic fertilization at a 50:50% ratio of P2O5 (SSLC). In the first cycle, soil fertility, foliar contents, production components, and yield were assessed. In the second cycle, soil fertility, foliar contents, production components, yield, nutrient accumulation, and heavy metal content in soil, plants, and chickpea seeds were evaluated. In the first study, it was observed that the phosphorus management practices (SS, LC, and SSLC) increased phosphorus levels and the sum of bases in the soil, leading to a 72% increase in chickpea productivity. However, in the second study, it was found that the inoculation with the mix of Bacillus spp. affected productivity by approximately 13.47%. Despite the increase in soil phosphorus levels due to phosphorus management practices, there was no influence on chickpea productivity. The total nutrient accumulation order in the aerial part was: N > K > P > Ca > Mg > S, with total average quantities of 206,47 kg t-1; 72,65 kg t-1; 42,48 kg t-1; 15,48 kg t1 ; 10,70 kg t-1; 0,44 kg t-1, respectively. Regarding the heavy metal assessments, it was observed that the inoculation of Bacillus spp. led to a decrease in chromium (Cr) levels in the soil. The inoculation also favored the reduction of lead (Pb) levels in chickpea leaves for LC and SSLC management practices. An increase in barium (Ba) and zinc (Zn) levels in the seeds was observed due to the application of LC; however, all evaluated metals in the seeds were found to be below the levels permitted by legislation. It is concluded that the use of composted sewage sludge in conjunction with Bacillus spp. can enhance soil fertility and increase phosphorus levels' availability in the soil, contributing to improved productivity of chickpeas.